2020
DOI: 10.1039/c9tc06334j
|View full text |Cite
|
Sign up to set email alerts
|

Deviatoric stress-induced quasi-reconstructive phase transition in ZnTe

Abstract: A new phase transition mechanism induced by deviatoric stress was found and named as “quasi-reconstructive” transition.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
13
0

Year Published

2020
2020
2025
2025

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(13 citation statements)
references
References 28 publications
0
13
0
Order By: Relevance
“…However, unlike the previous experimental confirmation of post-perovskite structure requiring significant strain and/or large atomic displacements, such reversible transformation in LiSbO 3 needs only relatively small atomic displacements, indirectly related to Γ 1 – and Γ 2 modes. Hence, it is neither fully reconstructive nor fully displacive, which should be called displacive-/quasi-reconstructive transition. , Although the Sb:A Pnma state possesses lower enthalpy under the pressure range of 55–145 GPa, the phase transitions between these two hexagonal phases more easily occur on experiment due to the nature of displacive-/quasi-reconstructive transition. However, the Sb:A Pnma state should be directly synthesized under high temperatures and high pressures via laser heating-driven reconstructive transition.…”
Section: Resultsmentioning
confidence: 99%
“…However, unlike the previous experimental confirmation of post-perovskite structure requiring significant strain and/or large atomic displacements, such reversible transformation in LiSbO 3 needs only relatively small atomic displacements, indirectly related to Γ 1 – and Γ 2 modes. Hence, it is neither fully reconstructive nor fully displacive, which should be called displacive-/quasi-reconstructive transition. , Although the Sb:A Pnma state possesses lower enthalpy under the pressure range of 55–145 GPa, the phase transitions between these two hexagonal phases more easily occur on experiment due to the nature of displacive-/quasi-reconstructive transition. However, the Sb:A Pnma state should be directly synthesized under high temperatures and high pressures via laser heating-driven reconstructive transition.…”
Section: Resultsmentioning
confidence: 99%
“…Non‐ambient studies of these systems revealed a number of phase transitions, [8, 9, 12–25] which can be partially attributed to the non‐hydrostatic conditions and stress generated beyond the hydrostatic limits of pressure‐transmitting media [26–28] . Naturally, there are numerous examples of materials with various structure types and dimensionalities that show differences in phase‐transformation pressures under hydrostatic and non‐hydrostatic conditions [29–31] . In general, shear stress is believed to reduce the nominal transition pressure due to either decrease of the height of the potential barrier or high‐pressure phase nucleation at new defects generated during plastic deformation, as discussed in a comprehensive review by Levitas [32] .…”
Section: Introductionmentioning
confidence: 99%
“…[26][27][28] Naturally,there are numerous examples of materials with variouss tructure types and dimensionalities that show differences in phase-transformation pressures under hydrostatic and non-hydrostatic conditions. [29][30][31] In general, shear stress is believed to reduce the nominal transition pressure due to either decrease of the heighto ft he potentialb arrier or high-pressure phase nucleation at new defects generated during plastic deformation,a sd iscussed in ac omprehensive review by Levitas. [32] In this study,w edecided to distinguish a group of cage compounds,f orming molecular crystals with high (cubic or hexagonal) symmetry.R elevant literature data are summarized in Table S1.…”
Section: Introductionmentioning
confidence: 99%
“…[26][27][28] Naturally, there are numerous examples of materials with various structure types and dimensionalities that show differences in phase transformation pressures under hydrostatic and non-hydrostatic conditions. [29][30][31] In general, shear stress is believed to reduce the nominal transition pressure due to either decrease of the height of the potential barrier or highpressure phase nucleation at new defects generated during plastic deformation, as discussed in a comprehensive review by Levitas. 32 In spite of these reservations, we decided to distinguish a group of cage compounds, forming molecular crystals with high (cubic or hexagonal) symmetry.…”
Section: Introductionmentioning
confidence: 99%